Association of Home and Ambulatory Blood Pressure With Cardiovascular Prognosis in Practice Hypertensive Outpatients. Issue 2 (17th November 2022) - Narita, Keisuke; Hoshide, Satoshi; Kario, Kazuomi
Abstract : Background: Although international guidelines for hypertension management recommend home and ambulatory blood pressure (BP) monitoring, few studies have assessed which is more useful in predicting cardiovascular incidence in hypertensive outpatients. Methods: We analyzed the association of home and ambulatory BP with cardiovascular prognosis in 1336 practice outpatients with hypertension who underwent both home and ambulatory BP measurements in the J-HOP study (Japan Morning Surge-Home Blood Pressure). Results: During the median 6.9 years of follow-up, 111 cardiovascular events occurred. Both home and ambulatory systolic BP (SBP) were associated with cardiovascular risk independent of office SBP (hazard ratio [95% CI] per 20 mm Hg of average morning and evening home SBP, 1.46 [1.11–1.93]; 24-hour ambulatory SBP, 1.41 [1.02–1.94]). Moreover, average morning and evening home SBP was also associated with cardiovascular risk even adjusted by 24-hour ambulatory SBP (hazard ratio [95%CI] per 20 mm Hg, 1.38 [1.01–1.87]), but 24-hour ambulatory SBP was not associated with cardiovascular risk adjusted by average morning and evening home SBP. Regarding this relationship, the model-fit was significantly improved by using the analysis of likelihood ratio, but that was not significant in the analysis using C statistics. Additionally, even in patients with well-controlled 24-hour ambulatory BP, uncontrolled morning home BP was associated with cardiovascular risks (hazard ratio [95% CI], 2.15 [1.02–4.50]). In patients with well-controlled average morning and evening home BP, uncontrolled ambulatory BP was not associated with cardiovascular risks. Conclusions: This study demonstrated the prognostic values of home and ambulatory BP in practice hypertensive outpatients. Our findings indicated the modest superiority of home BP compared to ambulatory BP to predict cardiovascular prognosis.